Innovative Administrative Practices and the Quality of Secondary Education in Aba, Abia State, Nigeria: A Mixed-Methods Study - Chukwuma Victoria Azuka; Christopher Chinedu Joseph; Blessing Ikechi Onyedum; Emmanuel Lucas Nwachukwu (Lembaga Yasin AlSys, 2026)
Weak administrative capacity remains a major factor contributing to the persistent decline in the quality of secondary education across urban South-Eastern Nigeria, underscoring the need for empirical investigation grounded in local realities. Drawing on Bolman and Deal’s four-frame organizational model, Creemers and Kyriakides’ dynamic model of educational effectiveness, and Rogers’ diffusion of innovations theory, this study examines the relationship between innovative administrative practices and educational quality in 12 public secondary schools in Aba, Abia State, Nigeria. A mixed-methods design was employed, integrating quantitative data from 240 teachers and administrators with qualitative data obtained through 15 semi-structured interviews with principals and vice principals from the same schools. The findings indicate a moderate-to-high level of adoption of innovative administrative practices (M = 3.62, SD = 0.74). These practices were strongly and positively correlated with educational quality (r = .68, p < .01) and explained 55% of its variance (R² = .55) after controlling for school performance and school size. Participatory leadership, digital integration, and data-driven decision-making emerged as the principal drivers of educational quality, although their implementation was constrained by limited resources and policy inconsistencies. The study concludes that innovative administrative practices are essential for strengthening school effectiveness and improving secondary education quality. These findings contribute empirical evidence on administrative innovation in resource-constrained educational settings and highlight the need for targeted leadership development and stronger institutional support in Abia State and comparable contexts.